Complete sequencing of the mitochondrial genome of tea plant Camellia sinensis cv. ‘Baihaozao’: multichromosomal structure, phylogenetic relationships, and adaptive evolutionary analysis - Zhiyin Chen; Zhiyin Chen; Zhiyin Chen; Zhiyin Chen; Zixu Wang; Zixu Wang; Zixu Wang; Zixu Wang; Wei Zhou; Wei Zhou; Wei Zhou; Wei Zhou; et al. (Frontiers in Plant Science)
IntroductionThis study reports for the first time the complete sequence characteristics of the mitochondrial genome of the tea plant cultivar Camellia sinensis cv. ‘Baihaozao’. It systematically unveils its multi-chromosomal structure, RNA editing patterns, and adaptive evolutionary mechanisms, providing critical theoretical insights into the structural complexity and evolutionary mechanisms of the tea plant mitochondrial genome.MethodsThe mitochondrial genome was fully analyzed using genome sequencing and annotation techniques. RNA editing sites were predicted to evaluate editing patterns. Codon usage bias analysis was conducted to identify high-frequency codons. Repeat sequence analysis was used to characterize dispersed and tandem repeats. Adaptive evolutionary analysis, based on Ka/Ks ratios, was performed to investigate gene selection pressures.ResultsThe mitochondrial genome consists of 11 linear chromosomes, with a total length of 909,843 bp and a GC content of 45.62%. A total of 73 functional genes were annotated, among which 14 variable genes (e.g., ribosomal protein coding genes) retain intact functions without pseudogenization, which is rare among Theaceae plants. RNA editing site prediction revealed significant spatial heterogeneity, with the cox1 gene being a hotspot containing 19 editing sites. Approximately 58.49% of editing events were concentrated on the second base of codons, and 48.61% of the sites resulted in amino acid changes from hydrophilic to hydrophobic. Codon usage bias analysis showed significant enrichment of high-frequency codons, including UUU (phenylalanine), AUU (isoleucine), and UUC (phenylalanine). The genome’s repeat sequences were predominantly dispersed repeats (70.6%), with forward and palindromic repeats of 30–40 bp being dominant. Tandem repeats exhibited significant distribution heterogeneity among chromosomes. Adaptive evolution analysis showed that most PCGs (protein-coding genes) had Ka/Ks ratios below 1 (ranging from 0.07 to 0.78), with the atp9 gene showing the lowest ratio (0.07), while the mttB gene exhibited a significantly higher Ka/Ks ratio of 3.48. Additionally, 1.62% of the mitochondrial genome sequence was homologous to the chloroplast genome, carrying 26 complete functional genes, including 15 tRNA and 2 rRNA genes.DiscussionCodon usage bias may be related to mutation pressure due to the high AT content of the genome or reflect adaptive selection pressures for translational efficiency. The Ka/Ks results align with the widespread purifying selection observed in mitochondrial genomes, while the high Ka/Ks ratio of the mttB gene suggests it might be under positive selection to adapt to environmental pressures. The evolutionary evidence of inter-organelle gene transfer highlights the homologous sequences between mitochondria and chloroplasts. Overall, these findings systematically elucidate the adaptive evolutionary mechanisms and functional regulation of the tea plant mitochondrial genome.